PENINGKATAN PEMAHAMAN SISWA SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 7 PEKANBARU TERHADAP UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Fahmi Fahmi; Rizana Rizana; Rai Iqsandri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The development of increasingly sophisticated information technology makes the world and life seem limitless and timeless. This of course leads us as users to always be wise and aware of the use and impact of using this technology. Especially in the current era of globalization, the use of technology isn’t limited to certain ages and circles anymore. This results in many factors that cause a child and teenager to be involved in criminal cases related to information and electronic transactions, one of which is the use of social media that makes news containing hate speech easily and quickly spread. In this community service program, it provides an understanding of the rules that must be obeyed and the legal impact on criminal acts of information and electronic transactions, especially regarding hate speech. The approach to solving partner problems with programs that have been mutually agreed upon within the period of realization of the service is counseling accompanied by dialogue, with work procedures to support the methods offered are counseling and dialogues are carried out in several meetings according to the needs of partners as long as they are still in the long term program time. Later in this service program, scientific articles will be produced in accordance with the proposed activity plan, while for partners it is increasing knowledge about information crimes and electronic transactions.Keywords: Law, Information and Electronic Transaction, Counseling.